Toughness distribution in complex PP/nanoclay injected mouldings - Pettarin, Valeria (2013)
The fracture performance of PP-nanoclay box-like injection mouldings obtained in double gated mould and by direct compounding of PP and a PP-based masterbatch was studied. Samples were observed by polarised light microscopy and characterised by DSC. Other samples were fractured using mode I double edge-notched tensile specimens. Their typically brittle fracture did not show neat in-plane crack propagation. The initial crack was branched and deviated out of the plane normal to the applied stress, and the fracture no longer followed the simple mode I. There is a tendency towards increasing the ductility and the deformation at break with the increase in nanoclay content. The fracture initiation does not depend on the nanoclay content or on the test piece location; nanoclay reinforcement increases the energy propagation release rate, GCP, away from the weld line. The results allow the proposal of a model for the micro-mechanisms acting in samples which in-turn depends on nanoparticle orientation.